The Number of Grafted Fragments Affects the Outcome of Testis Tissue Xenografting from Piglets into Recipient Mice - Sepideh Abbasi; Ali Honaramooz (Veterinary Medicine International)
To optimize the procedure for testis tissue xenografting, we grafted 2, 4, 8, or 16 small fragments of immature porcine testis tissue under the back skin of immunodeficient castrated mice (n=10 mice/group). At 8 months post grafting, the graft recovery rate did not differ between groups; however, not only the total but also the average graft weights were higher (by ∼12-fold and ∼2.5-fold, resp.) in mice receiving 16 fragments than those receiving 2 fragments (P<.05). The recipient mice with 16 fragments had the largest vesicular glands (indicators of testosterone release by the grafts) compared with those with 2 fragments (P=.007). The grafts in the group of 16 fragments also had more (P<.05) percentage of tubules with round spermatids than those of the group of mice receiving 2 fragments. Therefore, recipient mice can be grafted with at least 16 testis tissue fragments for optimal results.